The need to regulate pollution prevention measures as a priority in order to achieve greater efficiency in the environmental enforcement of mining and energy - Aldana Durán, Martha Inés (2016)
In terms of environmental protection the priority is the prevention of pollution before any other measure. However, should this protective measure be compulsory or voluntary for all those who affect the environment? Is recycling or energy efficiency required?.In this article, the author analyzes these issues based on comparative legislation, doctrine and jurisprudence. Similarly, focusing on the mining and energy issue, studies its national regulation and its correlation with the activity of the Peruvian environmental inspection agency.